The Dramaturgy of Public Policy on Raising Subsidized Fuel Prices in Indonesia (Policy Comparative Analysis Between 2013 and 2022) - Patria, Nezar; Irawanto, Budi; Abrar, Ana Nadhya (UI Scholars Hub, 2025)
This study examines the policy of raising subsidized fuel prices in Indonesia through a dramaturgical lens, employing discourse analysis as its methodology. Each fuel price increase triggers intense political debates, involving key governmental figures and eliciting diverse public responses. The research contrasts two pivotal periods: the policy decisions during President Susilo Bambang Yudhoyono's administration in 2013 and those under President Joko Widodo in 2022. Using a dramaturgical framework, the study analyzes the dimensions of scripting, setting, staging, and performance in policymaking, highlighting how each administration constructs distinct policy narratives. In 2013, the policy faced significant opposition and robust public discourse. In contrast, by 2022, media strategies were strategically employed to shape the narrative and mitigate dissent. The findings reveal contrasting approaches by the two administrations in managing the political and social consequences of the fuel price increases. These insights contribute to a deeper understanding of the dynamics of public policy in the context of economic and political challenges, emphasizing the critical role of communication strategies in the implementation of contentious policies.